A community health-coaching referral program following discharge from treatment for chronic low back pain - a qualitative study of the patient's perspective - Katharine Roberts; Melissa Baysari; Emma Ho; Paula Beckenkamp; Ye Tian; Matthew Jennings; Anita Amorim; Katherine Maka; Rachael Morton; Dragana Ceprnja; Mark Halliday; Manuela Ferreira; et al. (BMC, 2024)
Abstract Background Global policy and guidelines for low back pain (LBP) management promote physical activity and self-management yet adherence is poor and a decline in outcomes is common following discharge from treatment. Health coaching is effective at improving exercise adherence, self-efficacy, and social support in individuals with chronic conditions, and may be an acceptable, cost-effective way to support people in the community following discharge from treatment for LBP. Aim This qualitative study aimed to understand which aspects of a community over-the-phone health-coaching program, were liked and disliked by patients as well as their perceived outcomes of the service after being discharged from LBP treatment. Methods A purposive sampling approach was used to recruit 12 participants with chronic LBP, from a large randomised controlled trial, who were randomly allocated to receive a health coaching program from the Get Healthy Service® in Australia. Semi-structured interviews were conducted, and a general inductive thematic analysis approach was taken. Results The main themes uncovered regarding the intervention included the positive and negative aspects of the health coaching service and the relationship between the participant and health coach. Specifically, the participants spoke of the importance of the health coach, the value of goal setting, the quality of the advice received, the benefits of feeling supported, the format of the coaching service, and LBP-specific knowledge. They also reported the health coach and the coaching relationship to be the primary factors influencing the program outcomes and the qualities of the coaching relationship they valued most were connection, communication, care, and competence. The sub-themes uncovered regarding the outcomes of the intervention included positive impacts (a greater capacity to cope, increased confidence, increased motivation and increased satisfaction) and negative impacts (receiving no personal benefit). Clinical implications In an environment where self-management and self-care are becoming increasingly important, understanding the patient's experience as part of a coaching program is likely to lead to improved quality of health coaching care, more tailored service delivery and potentially more effective and cost-effective community-based care for individuals with chronic LBP in the community after being discharged from treatment. Trial Registration The GBTH trial was prospectively registered with the Australian New Zealand Clinical Trials Registry (ACTRN12620000889954) on 10/9/2020. Ethical approval was prospectively granted by the Western Sydney Local Health District Human Research and Ethics Committee (2020/ETH00115). Written informed consent was obtained from all participants. The relevant sponsor has reviewed the study protocol and consent form.